In silico design of a multi-epitope vaccine against Lyssavirus Phylogroup II Glycoproteins - Fabiha, Fahmida; Shadman, S. M. Salim (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology 2022.